Impact of l-Arginine Metabolism on Immune Response and Anticancer Immunotherapy - Kim, Sun-Hee; Roszik, Jason; Grimm, Elizabeth A.; Ekmekcioglu, Suhendan (Frontiers in Oncology, 2018)
The progression from neoplastic initiation to malignancy happens in part because of the failure of immune surveillance. Cancer cells successfully escape immune recognition and elimination and create an immune-suppressive microenvironment. A suppressive metabolic microenvironment may also contribute to ineffective T-cell function. Tumor progression is characterized by a complex network of interactions among different cell types that cooperatively exploit metabolic reprogramming. As we start to recognize that cancer cells use different metabolism processes than normal cells do, a better understanding of the functional mechanisms of the regulation and reprograming of the metabolic landscape in cancer cells is crucial to successful immunotherapy strategies. However, the exact role of metabolism in T cells and in the tumor microenvironment is not known. One pathway that plays an important role in the regulation of immune cell reactivity is arginine metabolism, which has complex cellular functions. L-arginine and its downstream metabolites (e.g., ornithine, citrulline) could be essential to T-cell activation and thus modulate innate and adaptive immunity to further promote tumor survival and growth. Identifying metabolic targets that mediate immunosuppression and are fundamental to sustaining tumor growth is key to increasing the efficacy of immunotherapies.